Effect of organic liquid foliar fertilizers on the quality of red cedar seedlings (cedrela odorata L.), in the nursery phase - Alvarez Ticllasuca, Adiel (2022)
The purpose of the research work was to evaluate the predominance of 2 types of organic liquid foliar fertilizer and 3 doses, in the quality of Cedrela odorata L seedlings. An Entirely Random Design was applied with a 2x3 factorial arrangement and 5 repetitions; the components under analysis were: element A: AFLF and AFLH, and component B: 50, 100 and 150 mL/20 L of water, generating 6 treatments plus a control; 525 seedlings were installed and evaluated over 5 months, after which the highest seedling elevation (19.70 cm) occurred with T5 (150 mL AFLF/20 L water) and the lowest elevation (18, 76 cm) with T1 (50 mL AFLF/20 L water), with high quality seedlings; the largest diameter (8.32 mm) was obtained with T4 (100 mL of AFLH/20 L water) and the smallest (7.41 mm) in T0, with high quality seedlings; show high quality of height/diameter interaction or solidity index; the seedlings of the treatments T0, T1, T3, T4 and T6, present high quality of the stem/root interaction and those of the treatments T2 and T5 average quality, the Dickson Quality Index indicates the average quality of the total number of seedlings treated.